Suicide attempt using zinc phosphide rodenticide: A case report and literature review - Nekoukar, Zahra; Moghimi, Minoo; Rasouli, Kimia; Hoseini, Aref; Zakariaei, Zakaria; Tabaripour, Rabeeh; Fakhar, Mahdi; Banimostafavi, Elham Sadat (Clinical case reports, 2021)
The patients with a history of intentional or unintentional consumption of rodenticide compounds, especially ZnP, it is necessary to assess ABG and abdominal radiography. In the patients with a history of intentional or unintentional consumption of rodenticide compounds, especially ZnP, it is necessary to assess ABG and abdominal radiography.